EFEKTIVITAS PERENCANAAN DAN PENGADAAN OBAT PUSKESMAS BADAN LAYANAN UMUM DAERAH (BLUD) DI KABUPATEN JEMBER - Rahmawati, Diana Aulia; Nita, Yunita; Hermansyah, Andi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
The Transition of Primary Healthcare Centers to Regional Public Service Agency (BLUD) status allows them to independently manage their finances, including medicine procurement. This change is expected to impact the effectiveness of planning and procurement. This study evaluated the effectiveness of medicine planning and procurement in Primary Healthcare Centers that had transitioned to BLUD status. The study used retrospective observations based on data from 2022 to June 2024. Samples were selected using purposive sampling based on inclusion and exclusion criteria. The independent variable in this study was the implementation of BLUD financial management, while the dependent variables included compliance with FORNAS, medicine stockouts, and excess medicines. The study involved 30 Primary Healthcare Centers and the KruskalWallis test was used for statistical analysis. The results showed that the average scores for all indicators did not meet the expected standards. After BLUD implementation, there was a decrease in medicine compliance with FORNAS, although it remained above the minimum performance standard of 80%, and a significant reduction in stockouts (p < 0.05). The percentage of excess medicines increased, but not significantly (p > 0.05). In conclusion, medicine planning and procurement were ineffective. The BLUD financial management model impacted medicine planning and procurement by reducing compliance with FORNAS, and decreasing stockouts.